Child health care nurses' experience of language screening for 2.5‐year‐old children: A qualitative study - Anna Lindgren Fändriks; Kjerstin Almqvist; Fredrik Hjärthag; Karin Pernebo (Wiley, 2023)
Abstract Aim To investigate the experience of Child Health Care Nurses (CHCNs) using language screening for 2.5‐year‐old children. Design An exploratory qualitative design with an inductive approach. Method Data were collected through semi‐structured, interviews with Swedish CHCNs who regularly performed language screening for children. The interviews were analysed by thematic analysis. Results Four themes were identified: 'The difficult visit', 'Explanations for language delay', 'Language screening across cultures' and 'Language screening with children exposed to adverse life events'. Patient or Public Contribution Our findings suggest that in routine care a modified procedure is used for the language screening of children aged 2.5 to secure the child's cooperation and to preserve an alliance with the parents. Consequently, the validity of the screening is called into question, particularly when it comes to children from families with origins outside the dominant culture and children exposed to adverse life events.